Sakhalin sturgeon Acipenser mikadoi (Acipenseridae): results of study and proposed measures for conservation of the species - V. N. Koshelev; N. V. Kolpakov (Известия ТИНРО)
All available data on sakhalin sturgeon Acipenser mikadoi are summarized. Its historical and modern habitats are described and their significant reduction is noted. Now the species is abundant in the Russian part of its range only — in the Tumnin River, where it is represented in commercial catches by two clearly different groups: large-sized juveniles (FL 43–68 cm) and mature fish (FL 135–169 cm). Juveniles of sakhalin sturgeon migrate during their first years, as their osmoregulatory system forms, to the lower reaches of Tumnin, to the internal estuary, and then to the Datta Bay, the Tatar Strait and the Japan Sea. When returned to the Tumnin, the spawners of sakhalin sturgeon have the length 135–169 cm (n = 29) and weight 15–36 kg. Sex ratio among the caught mature fish is 13.0 : 4 or 3.2 : 1 for females : males, on average. Fecundity of the sturgeon females sampled for artificial reproduction varied from 44.8 to 150.0 thousand eggs, on average 87.3 ± 12.1 . 103 eggs. In total, 17 mature spawners of A.mikadoi were caught in the Tumnin River in 2006–2019 for artificial reproduction (♀ = 13, ♂ = 4), 13 individuals were injected, among them 4/5 of females and 2/3 of males gave high-quality sex products. Producers of this species were distinguished by high survival during manipulations of fish breeding (100 %). Their progeny had low survival, both embryos during incubation and juveniles during rearing; the survival rate for the stage from eggs laid for incubation to juveniles with weight 3.4–7.0 g was 1.85 %. The low survival was supposedly reasoned by combination of unfavorable environmental factors and fish-breeding manipulations. Totally 11,214 juveniles of sakhalin sturgeon with weight from 3.4 to 7.0 g were released into the natural habitat (Tumnin river) in 2007, 2008, 2015, 2017, and 2019. At Anyui sturgeon fish hatchery, the broodstock of sakhalin sturgeon with 274 individuals of 5 ages is created and operated successfully. The male sturgeons in the hatchery mature at the age of 8 years. Here, 11 males of the 2007–2008 year-classes participated in the spawning in 2015–2019. Re-maturation of males was not recorded yet. For the broodstock formation in other fish hatcheries, 200 juveniles of sakhalin sturgeon were transferred to them. To preserve the species, a set of measures is proposed to strengthen its protection and to enhance its artificial reproduction, including the fry releasing into the rivers of the mainland coast, Sakhalin Island, and Japan.